Uniting States voluntary union in world politics - Parent, Joseph M. (New York ; Oxford : Oxford University Press, 2011)
What causes states to politically unify voluntarily? This text develops a realist explanation of voluntary union and argues that unions are the balancing coalitions of last resort.
Description based on print version record.
Includes bibliographical references.
Keywords: Federal government; Confederation of states; Constitutional history -- United States; European federation; Latin American federation